Investigating the Behavior of the Plastic Concrete Made with Different Types of Fibers with an Approach to the Mixing Plans of Plastic Concrete - Abolfazl Ostovarzijerdi; Akbar Ghanbari; Mohammad Karkon (Civil Engineering Journal, 2019)
The complicated nature of the plastic concrete’s behavior compared to conventional concrete has led to the study of the behavior of the plastic concrete and the advent of suitable solutions to improve the behavior of the concrete due to the abundance of plastic concrete in the construction of cut-off walls under the dams. For the purpose of a practical study, at first, the mixing plan of the plastic concrete cut-off wall in Nargesi dam was investigated. Then, 22 primitive mixing plans were identified and labeled in the laboratory to identify the optimal mixing plan in accordance with the required technical criteria. After selecting the desired optimal design, to investigate the effect of the fiber on the behavior of this concrete, %0.19 and 0.38% volumes of polypropylene, hooked metal and corrugated metal fibers were used; hence, 168 samples were presented. Compressive strength for the ages of 7, 28, 42 and 90 days with elasticity modulus as well as corresponding stress-strain curves and tensile strength for 90-day age were investigated. The results indicated that the extremely high compressive strength and modulus of elasticity have a very high impact on the amount of bentonite and the ratio of water to bentonite so that with increasing these two values, the compressive strength and modulus of elasticity decrease significantly. The results indicated that using fibers increases deformation which is more evident in samples made with polypropylene fibers. The results also showed that the compressive strength and modulus of elasticity of plastic concrete is increasing linearly with time, and the elastic modulus growth rate is lower than the compressive strength due to the increase in the duration of time, and in other words, the plastic state concrete changes less over time.